MOTIVASI DAN DAYA SERAP MATERI BANGUN DATAR DALAM PEMBELAJARAN DENGAN PENGANTAR BAHASA DAYAK MA’APH - Ferianti, Flesia Welly; Linda Dwi Saputri; Aprima Tirsa (AL KHAWARIZMI: Jurnal Pendidikan Matematika, 2025)
Abstract Students in the learning process still need their mother tongue to help understand the meaning and intent comprehensively, because some students are still interfered with by their mother tongue. The mother tongue used at SMPN 2 Nanga Mahap is Ma'aph. This study aims to increase motivation and absorption of flat shape material with an introduction to the Ma'aph Dayak language. The method used is research and development of 4-D models. The products developed are in the form of RPP and LKPD which contain the mother tongue. Based on the results of the development, the percentage of RPP validation is 86.7% and LKPD is 88.6% which is classified as very valid or feasible to use. 75% of students' motivation is included in the good category and the absorption capacity is fulfilled classically, namely 86% of students who achieve the KKM score. This shows that learning the material of flat shapes with the introduction of the Ma'aph Dayak language increases students' motivation and absorption. For researchers who want to apply mother tongue learning tools, it is expected that they must master the local language well and understand the characteristics of the research subject. Keywords: Mother Tongue, Students' Motivation, Absorption